An investigastion of factors affecting salaried and waged taxpayer compliance behavior: evidence from Libya - Al Haj, Alhassan Belkasem Mo (2016)
Convincing taxpayers to comply with the tax regulations has been the main challenge of Libyan tax authority. Even though tax is one of the important revenue sources after oil in Libya, over the last five years, tax collection has been on decrease trend. The main purpose of this study is to examine the effect of tax knowledge, tax complexity, public governance quality and perception of government spending on salaried and waged taxpayer compliance behavior in Libya. The study was guided by cognitive theory and social exchange theory which explain the effect of noneconomic factors. Using survey method, a total of 400 questionnaires were distributed among Libyan students in Malaysia since they are considered part of individual taxpayers in Libya. The findings indicate positive and significant relationship between tax knowledge, public governance quality, perception of government spending and taxpayer compliance behavior, except tax complexity that shows a significant negative relationship with taxpayer compliance behavior. The study recommends that the tax legislations should be reviewed and simplified besides promoting tax knowledge among taxpayers. In addition, Libyan government should also place attention on public governance quality and government spending in order to increase taxpayer compliance behavior.